ChemInform Abstract: Tandem Hydroformylation—Biginelli Reaction. Issue 49 (3rd December 2013) - Fuchs, Daniela; Nasr‐Esfahani, Mahboobeh; Diab, Lisa; Smejkal, Tomas; Breit, Bernhard
Abstract Alkenes and synthesis gas readily furnish C1‐elongated aldehydes.